2001
DOI: 10.1016/s0092-8674(01)00617-1
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Bound States of GroEL Captured by Cryo-Electron Microscopy

Abstract: The chaperonin GroEL drives its protein-folding cycle by cooperatively binding ATP to one of its two rings, priming that ring to become folding-active upon GroES binding, while simultaneously discharging the previous folding chamber from the opposite ring. The GroEL-ATP structure, determined by cryo-EM and atomic structure fitting, shows that the intermediate domains rotate downward, switching their intersubunit salt bridge contacts from substrate binding to ATP binding domains. These observations, together wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
313
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(328 citation statements)
references
References 46 publications
14
313
1
Order By: Relevance
“…1). During this transition, apical domains move up Ϸ10°and rotate counterclockwise Ϸ25° (33). To ascertain the effect of ATP binding on the SP conformational change we considered three values (see SI Table 1 Distribution functions characterizing the global structural features of the SP at 300 K. (a) Probability distribution P(R g) of the radius of gyration (Rg) of the SP in the bulk.…”
Section: Sp Capture Kinetics Involves Multiple Time Scales and Mechanmentioning
confidence: 99%
“…1). During this transition, apical domains move up Ϸ10°and rotate counterclockwise Ϸ25° (33). To ascertain the effect of ATP binding on the SP conformational change we considered three values (see SI Table 1 Distribution functions characterizing the global structural features of the SP at 300 K. (a) Probability distribution P(R g) of the radius of gyration (Rg) of the SP in the bulk.…”
Section: Sp Capture Kinetics Involves Multiple Time Scales and Mechanmentioning
confidence: 99%
“…The fluctuating salt-bridge interactions, visible in recently reported EM densities [12], involve residues that are conserved in all GroEL sequences, thus highlighting their functional importance [41]. At the intra-ring level, the R197-E386 salt bridge between the intermediate and the apical domains of two adjacent subunits that is found in the unliganded (apo) state is replaced by K80-E386 in the ATP-bound state [34], whereas E255-K207 switches to E255-K245 in the ATP-bound state (Fig. 3B) [12].…”
Section: Atp Bindingmentioning
confidence: 89%
“…Cryo-EM studies further showed an altered interaction pattern at the inter-ring interface after ATP binding [34,38], which is interpreted as the main mechanism for negative inter-ring cooperativity. Helix D, located in the equatorial domain, couples the ATP binding site of a subunit in one ring to an adjacent subunit of the opposite ring (Fig.…”
Section: Atp Bindingmentioning
confidence: 91%
See 1 more Smart Citation
“…Leu 400 and Arg 404 in the T state (Protein Data Bank code 1OEL) (31), R state (code 2C7E) (32), and RЉ state (code 1AON) (1) of EC GroEL are shown in Fig. 5.…”
Section: Groel1 From C Pneumoniae Acts As a Chaperonin-mentioning
confidence: 99%